Biogas Production from Tofu Waste to Improve the Environmental Performance of Tofu Industry - Wagiman Wagiman; Icha Rizkia Ardaniswari; Welly Prakoso Nugravianto (APTA and DTIP FTP UGM, 2020)
The tofu industry produces solid waste and wastewater that still contain high protein which suitab le as raw material for biogas. Conversion of waste into biogas will contribute to improving the en vironmental performance of small and medium scale industries to increase the added value for the industry. This research was aimed to develop biogas production process by utilizing wastewater a nd solid waste from tofu industry. There were three stages of process development: biogas product ion from wastewater (as control), biogas production from solid waste, and biogas production from a combination of solid waste and wastewater. The results of the production process were evaluate d based on the volume and its added value on both financial and environmental performance. The output from this research was the model of solid waste and wastewater processing for small and medium scale tofu industry. The result showed that the addition of solid waste of tofu and the sour ce of microorganisms from cow manure was able to produce much larger volume of biogas as muc h as 715 ml in shorter time of 7 days. Another result of this research was to make a better environ ment in tofu industry which is seen from the aspects of health and aesthetic.